EKSTRAK KULIT BUAH KOPI ALTERNATIF PESTISIDA NABATI SEBAGAI PENGENDALI ULAT PADA TANAMAN PAKCOY (Brassica rapa subsp. chinensis (L.) Hanelt) - Harlita Harlita; Ardanicha Mauliyana (Universitas Sebelas Maret, 2021)
This research aims to find out the effect of coffee beans shell extract as vegetable pesticides seen by the capability of pressing food activity and increasing caterpillar mortality to mustard greens. This research took place in the Biology Education Laboratory University of Sebelas Maret from May until July 2021. This research using an experimental method and Completely Randomized Design with two steps of tests there are preliminary test and primary test. The Preliminary test is a toxicity test to find out LC50 that is 15%, for the next is used to determine primary test concentration. There are five treatments of mortality test and food activity test that is an increment of coffee beans shell extract with the concentrations 0% (P1), 10% (P2), 15% (P3), 20% (P4), and 25% (P5) with five repetitions of a caterpillar. Toxicity test data were analyzed by probit analysis. Mortality test data is analyzed with regression linear and food activity test is analyzed by one-way Anova at significance level 5%, and continued with Tukey test. The research result is coffee beans shell extract has a significant effect on caterpillar mortality, with the higher mortality is P4 treatment that is 1005. The extract is also has a significant effect on food activity with the lower food activity at P5 treatment that is 8%.